[PP.19.26] PULSE WAVE SPEED - A METHOD IN MONITORING OF HYPERTENSION IN CLINICAL PRACTICE. (September 2017) - Ayoub, J.; Machado, I.
Abstract : Objective: This work aims to demonstrate the relationship between Pulse Wave Velocity (PWV) and central Aortic pressure (PaO) in the office of the patients, since it expresses the relationship between stiffness, elasticity and arterial compliance. Design and method: The study was carried out from the data collection of the Institute of Cardiovascular Diseases of Rio Preto and State College of Medicine São José do Rio Preto – Sao Paulo - Brazil. We evaluated 123 patients receiving their treatment, of which 98 males and 25 females, which in turn were subjected to evaluation of computerized automatic Sphygmocor® (Model - IN 3, Australia - Atcor Medical Pty LTd) avaliando- is the pulse wave velocity (PWV), Aorta pressure (PaO). Patients were analyzed and not with high blood pressure (HAS), coronary artery disease (CAD) and diabetes (DM). Results: After analysis of the results from the Pearson correlation coefficient (r) and Spearman (p), we can conclude that there was a weak correlation, but positive (r = 0.2237) and significant between Hypertension and pulse wave velocity (PWV) (p = 0.01); weak correlation, but positive (r = 0.2200) and significant between Coronary Artery Disease (CAD) and age (p = 0.0145); weak correlation, but positive (r = 0.1814) and significantly between diabetes and VOP (P = 0.0447), and weak correlation (r = 0.02760), but significant between CAD and VOP (p = 0.7614). Conclusions: Therefore, the analysis of pulse wave velocity (PWV) and central aorta pressure (PaO) has been presented as simple diagnostic method, non-invasive and sensitive for assessing arterial stiffness. It is set thus, the importance of identifying individuals at high risk for such changes and to determine appropriate therapeutic intervention.